Production of the organic cocoa in the amazon: a case study of the amazon organic products cooperative – COPOAM - Vronski, Magda; Maia Olimpio, Silvia (REBRAE, 2016)
This article aims to show the results and discussions of the exploratory descriptive research carried out by the Cooperative of Organic Products of the Amazon (COPOAM), which is composed of cocoa producers part of agricultural families cooperative located in the Transamazon Highway region, state of Pará. The main purpose of this research is to illustrate the producer’s strategies towards production and marketing of organic products. This work also demonstrates the cooperative's market expansion based on its formalized contracts and sustainable development practices, which can stimulate initiatives that promote the good use of natural resources in the Amazon, as well as participatory management of the territory. Such actions contribute to local development in a needy and anthropized region.